Encyclopedia of drugs, alcohol, & addictive behavior - Carson-DeWitt, Rosalyn (Macmillan Reference USA, 2001)
Consider a smattering of statistics: in 1999, 10.3 million people (4.7% of the American population) ages 12 years or older were dependent on illicit drugs or alcohol; in 1998, it was estimated that approximately 19,000 alcohol induced deaths occur annually in the United States; in 1993, it was reported that 13,984 people were killed in alcohol-related motor vehicle accidents; 3,765 of these individuals had not been drinking themselves; in 1998 16,926 deaths were attributed to drug-induced causes; in 1998, chronic liver disease and cirrhosis grant as the 10th leading cause of death in the United States; fetal alcohol syndrome affects one in every 600-750 births, and is currently the leading cause of mental retardation, beating out previous contenders such as down syndrome and spina bifida; economic cost to society related to alcohol and drug abuse projected at nearly $246 million in 1992; projections for 1995 suggests that economic costs related to alcohol and drug abuse would reach over $276 million; smokers ages 18-25 have a fourfold increased likelihood of illicit drug use compared to their non-smoking peers; smokers ages 12-17 have a sevenfold increased likelihood of illicit drug use compared to the non-smoking peers; in 2000, the United States put together an emergency aid package to Colombia, totaling $1.3 billion, intended in part to address the issues of drug trafficking between Columbia and the United States; in 1999, the annual cost for problem and pathological gambling reached $5 billion, with lifetime costs projected at $40 billion associated with decreased productivity, social service costs, and creditor losses; drugs, alcohol, and addictive behaviors have enormous ramifications on a global scale, and include political, economic, legal, social, and public health issues...